An 18-Month Follow-up, Randomized Comparison of Effectiveness and Safety of Two Hyaluronic Acid Fillers for Treatment of Moderate Nasolabial Folds. Issue 1 (January 2017) - Rzany, Berthold; Bayerl, Christiane; Bodokh, Isaac; Boineau, Dominique; Dirschka, Thomas; Queille-Roussel, Catherine; Sebastian, Michael; Sommer, Boris; Edwartz, Carolina; Podda, Maurizio
Abstract : BACKGROUND: Hyaluronic acid (HA) filler injection is a popular nonsurgical aesthetic procedure. OBJECTIVE: To compare the effectiveness and safety of 2 hyaluronic acid fillers (HAEC and HARES ) for treatment of moderate nasolabial folds (NLFs). MATERIALS AND METHODS: This was an evaluator- and subject-blinded split-face study. HAEC or HARES was randomly assigned to the left or right NLF at baseline. Retreatment was performed after 9 months; follow-up extended to 18 months after baseline (9 months after retreatment). Effectiveness assessments included the Wrinkle Severity Rating Scale (WSRS) and subject preference. Safety assessments included adverse events (AEs) and local tolerability symptoms recorded by subjects during 3 weeks after treatment. RESULTS: HAEC was noninferior to HARES measured as mean change from baseline in WSRS score at 6 months. Mean WSRS score change from baseline was similar between products up to 18 months. A majority of subjects (>70%) were still responders at 18 months (after retreatment at 9 months). The volume required at retreatment was approximately two-thirds of that at baseline. There was no difference in subject preference between products. Both fillers were well tolerated and associated with few treatment-related AEs. CONCLUSION: HAEC and HARES were effective and well tolerated for treatment of moderate NLFs.